Reciprocal Borrowing Programme for Warsaw academic libraries (BiblioWawa/SWW) – description and analysis on the example of the Main Library of the Medical University of Warsaw - Klaudia Makowska (Forum Bibliotek Medycznych, 2020)
The project of university libraries of Warsaw – BiblioWawa/SWW - offers the possibility to access the participating libraries’ collections on a reciprocal basis. The first part of the article presents the general project overview including the rules of joining and participating in the project. Further in the article, the author presents the analysis of 2 years of the project’s operation on the example of the Main Library of the Warsaw Medical University and attempts to answer the question, “what is the level of interest in the project among its users” as well as what opportunities and development needs are associated with this project.